Inclusions, Meetings and Landscapes - Skovsmose, Ole [UNESP] (My University, 2019)
In this chapter, I explore the very notion of inclusion. Apparently, it is a straightforward notion, as it always seems praiseworthy to work for inclusion and, certainly, to do so in an educational domain. I want to show, however, that it is only at its semantic surface that inclusion is forthright but that it is actually a contested concept. Such a concept can receive different interpretations and be brought into action in very different discourses. A contested concept represents controversies that can be of profound political and cultural nature. Every time one talks about inclusion, one needs to ask: Inclusion into what? Inclusion could mean inclusion into questionable patterns and structures. This also applies to inclusive mathematics education. Furthermore, one needs to ask: Inclusion of whom? Inclusion always concerns some groups of people to be included. However, inclusion can be accompanied by the most problematic discourses, for instance, referring to who are ŉormal’ and who are not. Questioning the notion of normality brings me to reinterpret inclusive education as an education that tries to establish meetings amongst differences. Consequently, it becomes crucial for an inclusive mathematics education to elaborate inclusive landscapes of investigations. Such landscapes facilitate inquiries; they are accessible for everybody; and they make collaborations possible. The construction of such landscapes, however, is a contested activity.
Keywords: Inclusion; Inclusive landscapes of investigation; Landscapes of investigation; Meeting